The Effect of Giving Moringa Leaf Extract (Moringa oleifera) in Drinking Water on Primal Cut in Broiler Chicken - Dami, Yusrin A. S. L; Suryatni, Ni Putu F.; Theedens, Jonas F. (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
The purpose of this study was to determine the effect of giving moringa leaf extract (moringa oleifera), through drinking water, on primal pieces in broiler chickens. This study used 96 day old chicks of CP 707 strain produced by PT Charoen Pokphand Indonesia. The experimental design used was a completely randomized design (CRD) with 4 treatments and 6 replications. Each repetition consisted of 4 broiler chickens. The treatments tested were P0: Drinking water without Moringa extract (control), P1: 40 ml Moringa extract/L of drinking water, P2: 80 ml Moringa leaf extract/L of drinking water, P3: 120 ml Moringa extract /L of drinking water. The variables studied were chest percentage, thigh percentage, back percentage, and wing percentage. The results of statistical analysis showed that giving Moringa leaf extract in drinking water had a significant effect (P<0.05) on chest percentage but had no significant effect (P>0.05) on wing percentage, thigh percentage and shoulder percentage. Based on the results of the study it can be concluded that giving Moringa leaf extract up to 120 ml/L of drinking water can increase the percentage of the chest but has not made any changes to the percentage of the wings, the percentage of the thighs and the percentage of the back.